PENGARUH BEBERAPA FAKTOR STATUS SOSIAL EKONOMI TERHADAP KINERJA KARYAWAN KOPERASI CU CINTAKASIH TIGAPANAH KABUPATEN KARO - Tinambunan, Anitha P. (UNIKA Santo Thomas, 2020)
This study aims to 1. Determine whether the level of education, income and type of work has a positive and significant effect on the performance of the employees of the Cooperative CU Cinta Kasih Tigapanah Kab. Karo; 2. Knowing which factors are the most dominant influence on the performance of employees of the Cooperative CU Cinta Kasih Tigapanah Kab. Karo Data collection techniques carried out through interviews, documentation and questionnaires. The study population was all employees of the Cooperative CU Cinta Kasih Tigapanah Kab. Karo numbering 200 people (July 2019). The sampling technique uses Proportional Random Sampling where the research sample is taken from each work field in the Cooperative CU Cinta Kasih Tigapanah Kab.Karo. Based on the results of the F test it is known that the value of Fcount is 44,291> Ftable 3,145 with a significance level of 0,000